Evaluation of women's smoking and hookah use in the context of gender: A men's perspective - Sen, Mehmet Ali; Ak, Eda Yakit; Yarasir, Ezgi (Routledge Journals, Taylor & Francis Ltd, 2024)
Aim: This study aims to evaluate women's smoking and hookah use from a male perspective in the context of gender. Method: The study was completed with a total of 716 male participants. Data were collected with the Introductory Information Form, Fagerstr & ouml;m Nicotine Dependence Test (FNDT), Lebanon Hookah Dependence Scale (LHDS-11), and Social Gender Perception Scale (SGPS) and evaluated with the correlation between them. Results: The mean age of the male participants was 34.93 +/- 12.95 years. Among them, 42.4% had completed high school, and 50.8% were married. A significant correlation was observed between the SGPS total scores of the participants and the following variables: age, marital status, employment status, and the type of family in which the participants were raised (p < 0.05). The participants did not perceive a woman who smoked cigarettes or a hookah to be free or strong. Additionally, they asserted that a woman who smoked was incapable of having healthy children. The total score on the FNDS for the male participants was found to be positively correlated with the LHDS-11 (r = .372) and negatively correlated with the SGPS (r = -0.186). The correlation between the LHDS-11 total score and the SGPS was found to be very weak and negative (r = -0.088), with a p-value less than 0.05. Conclusion: The findings indicated that male respondents perceived women's smoking and hookah use to be incongruent with social norms. It was determined that the participants generally evaluated cigarette and hookah use negatively, citing social reasons as the primary motivation rather than health concerns.
Keywords: Smoking; tobacco; hookah; men; gender